Transformation of the Concept of Jihad in Historical Lens - Fithri, Askini Ainul; Jamalullel; Jubaedah; Hajam (International Journal of Islamic Studies Issues, 2025)
This article discusses the transformation of the concept of jihad in Islam through a historical approach, from the religious struggle that is integral in Islamic history to a narrowed interpretation that often leads to violence and terrorism. The main aim of this research is to provide an in-depth and systematic understanding of jihad, as well as how this concept has changed over time. The method used in this research is descriptive qualitative, where the authors analyze data from various library sources, including books, journals, and articles related to jihad. Using a historical approach, the authors explore how the meaning and practice of jihad has changed over time, thereby providing a deeper context regarding the development of the concept of jihad in Islamic history. The results obtained show that jihad actually has broader and more complex dimensions than is often perceived in the conrext of violence. This research also highlights the importance of religious education and interfaith dialogue to bulid a better understanding of jihad in the modern era. For further research, it is recommended that a more in-depth study be conducted on the application of jihad values in the current social and political context, as well as identifying ways to educate the public about the true meaning of jihad as as struggle for good.